Common Problems in Communication of Non-English Majored Freshmen at A University in Vietnam (British Journal of Multidisciplinary and Advanced Studies, 2024)
Currently, Vietnam is in the phase of opening the economy and expanding cooperation with other countries in the region and around the world. There are many foreign investors as well as international tourists who will choose Vietnam as their destination. Meanwhile, there have been many research articles and articles from the past five years showing that although Vietnamese youth learning English as an official subject at school, they rarely use it when communicating with foreigners. Communication can be said to be the most difficult skill for English learners, especially non-majors. Communication skills require learners to master many factors, especially listening and speaking skills. However, for non-major students, learning English in class is mainly about doing theoretical exercises and studying to pass the subject, so English communication is really a challenge. Therefore, students encounter many problems in learning and practicing English communication. The study, “Common Problems in Communication of Non-English Majored Freshmen at a University in Vietnam,” will show the problems that the first-year non-English majors often encounter in English communication. The participants are 137 students in the classes Finance and Banking, Multimedia Communication, Construction Industry at Tay Do University in Cantho City in Vietnam. The main instruments are a questionnaire and an interview paper. The findings of the research will indicate that freshmen could face problems in linguistics, background knowledge, psychology, and environment. Thanks to the results, students will find the good ways to improve their English communication skills.